Intention to continue professional work after reaching retirement age and its determinants - Olejnik, Iwona (Zamiary kontynuacji pracy zawodowej poosiągnięciu wieku emerytalnego i ich determinanty, 2017)
In recent years, discussions concerning retirement age have focused mainly on its extension. The rise of interest in this issue is caused by demographic changes and the resulting problems faced by the system of retirement provision. Apart from increasing retirement pension premiums or decreasing the replacement rate, regular extending the retirement age is one of the ways of balancing the difference between the proceeds from premiums and the obligation to pay pensions. In view of the above, the aim of this article is to specify the factors influencing the intention to continue professional work after reaching retirement age (these intentions are measured by means of expectations towards the amount of money acquired for work continued in retirement). These determinants were identified by comparing the results obtained by means of two methods: linear regression and logistic regression. The article includes the results of representative survey studies carried out in 2014 in Poland on a randomised sample of 1163 households. The results of the study suggest that the determinants of the continuation of professional work after reaching retirement age include, in particular: age, education, occupation, household status, state of health, the perceived “proper age” to start saving up additionally for retirement and relations with children. The article was written within the research project by National Science Centre “Saving Practices and Financial Pension Security in Households – Determinants, Attitudes, Models” (No. UMO- 2012/05/B/HS4/04183)
Ekonometria = Econometrics, 2017, Nr 2 (56), s. 28-41
Keywords: retirement age; consumer behaviour; linear and logistic regression; wiek emerytalny; zachowania konsumentów; regresja liniowa i logistyczna